Sunteți pe pagina 1din 5

## ENGIANA Quiz 1 0917 736 1385

I. Multiple Choices: For each item, choose the 6. Which of the following equations is a linear DE?
letter of the best answer. A. i C. iii
1. This type of differential equation contains only B. ii D. iv
one independent variable. 7. Which of the following is an ordinary
A. Ordinary Differential Equation differential equation with homogeneous
B. Partial Differential Equation coefficients?
C. Complete Differential Equation A. x4 + (2 xy3 − x2 y 2 )dx − (5x3 y + 7 y 4 )dy = 0
D. None of these
2. This type of differential equation contains two
B. (x 5
+ 3x 2 y 3 + y 5 ) dx − x 4 ydy = 0

## or more independent variables. C. x2 dx + (6 y 2 − x2 + 3)dy = 0

A. Ordinary Differential Equation D. ( x ln y + xy ) dx + ( y ln x + xy )dy = 0
B. Partial Differential Equation
8. Solve the linear equation:
C. Complete Differential Equation
dy y
D. None of these + = x5
dx x
3. What is the order and degree of the differential
x7 x7
equation: A. xy = +C C. x5 y = +C
7 7
 d4y 
2
 dy 
3x  4  + 7 x3   − x 4 y = 0 x6 x6
 dy   dx  B. xy = + C D. x y = + C
5

7 7
A. 4th order, 5th degree
9. Solve: xy '(2 y − 1) = y(1 − x)
B. 5th order, 4th degree
A. ln( xy) = 2( x − y) + C
C. 4th order, 1st degree
D. 1st degree, 4th order B. ln( xy) = x − 2 y + C
For numbers 4-6 C. ln( xy) = 2 y − x + C
i. 13 ydx = ( x 7 + 3) dy D. ln( xy) = x + 2 y + C
10. Determine the differential equation of the family
ii. 3x2 ydx + (100 + x3 )dy = 0
of lines passing through (1,43).
iii. (13 y − y 3 ) dx + ( x 7 + 3) dy = 0 A. ( y − 1) dx − ( x − 43) dy = 0
iv. ( 3x 2 − y ) dx + (100 + x 3 ) dy = 0 B. ( y − 43) dx − ( x − 1) dy = 0
4. Which of the following equations is an exact C. ( x − 43) dx − ( y − 1) dy = 0
DE?
A. i C. iii D. ( y − 43) dy − ( x − 1) dx = 0
B. ii D. iv
5. Which of the following equations is a variable
separable DE?
A. i C. iii
B. ii D. iv

## For tutorials, text:

1
<name>, <subject>, <preferred date and time>, <no. of tutees> www.wix.com/syntaxdlsu/syntax
and send to 0917 736 1385.

## II. Problem Solving. Solve the following

differential equations.
1. ( x + y ) dy = ( x − y ) dx
1
2. xdy + ydx + dx + 3 y 2 dy = 0
x
dy
3. x + 2 y + y ln x = 0
dx
dy
4. ( cos x ) + ( sin x ) y = sin x , y ( 0 ) = 
dx
5. (y− )
x 2 + y 2 dx − xdy = 0

## For tutorials, text:

2
<name>, <subject>, <preferred date and time>, <no. of tutees> www.wix.com/syntaxdlsu/syntax
and send to 0917 736 1385.

## ENGIANA Quiz 1 0917 736 1385

ln x + ln ( v 2 + 2v − 1) = c
1
I. Multiple Choices 2 ln x + ln ( v 2 + 2v − 1) = 2c = k
1. A 6. D
2. B 7. B ln x 2 ( v 2 + 2v − 1) = C
3. C 8. A x 2 ( v 2 + 2v − 1) = e k = C
4. B 9. D
5. A 10. B
Substitute to original variables:
II. Problem Solving 
2  y
2
 y 
x   + 2   − 1 = C
1. ( x + y ) dy = ( x − y ) dx  x   x  

## This is a homogeneous differential equation. Final answer:

Let y = vx ; dy = vdx + xdv y 2 + 2 xy − x 2 = C or x 2 − 2 xy − y 2 = C

## Substitute and simplify: 1

( x + vx )( vdx + xdv ) = ( x − vx ) dx 2. xdy + ydx + dx + 3 y 2 dy = 0
x
x (1 + v )( vdx + xdv ) = x (1 − v ) dx Rearrange to standard form:
 1
(1 + v )( vdx + xdv ) = (1 − v ) dx (
 y +  dx + x + 3 y dy = 0
 x
2
)
vdx + xdv + v ( vdx + xdv ) = dx − vdx
vdx + xdv + v2dx + vxdv = dx − vdx The equation is an exact differential equation
2vdx − dx + v2 dx + vxdv + xdv = 0 since:
( 2v − 1 + v ) dx + x ( v + 1) dv = 0
2
M N
= =1
x y
 2v − 1 + v 2  x ( v + 1)
  dx + dv = 0
 x ( 2v − 1 + v ) 
2
x ( 2v − 1 + v 2
)
  Differentiate function M and solve for F:
( v + 1) dv = 0 F
dx
+ 2 = x + 3y2
x ( v + 2v − 1) y
F =  ( x + 3 y 2 ) dy = xy + y 3 + g ( x )
Integrate:
dx 2 ( v + 1) Equate obtained function to N
 x + 2  ( v2 + 2v − 1)dv = 0 F g ( x ) 1
= y+ = y+
x x
dx 1 ( 2v + 2 ) dv = 0 x
 +  2
x 2 ( v + 2v − 1)
g ( x ) 1
=
x x

## For tutorials, text:

3
<name>, <subject>, <preferred date and time>, <no. of tutees> www.wix.com/syntaxdlsu/syntax
and send to 0917 736 1385.

## ENGIANA Quiz 1 0917 736 1385

Integrate: dz
+ P ( x) z = Q ( x)
1
 dg ( x ) =  x dx
dx

g ( x) = ln x + C Integrating factor:
1
 = e = e  x = eln x = x
P ( x ) dx dx

Substitute g(x):
F = xy + y 3 + g ( x ) = xy + y 3 + ln x + C = 0
Apply the solution  z =  Q ( x )  dx + C :
xy + y 3 + ln x = C
− ln x
xz =  ( x ) dx + C
2x
1
y ( x + y 2 ) + ln x = C z = −  ln xdx + C
2x
1 1
z = −  x ( ln x ) − x  + C = − ( ln x − 1) + C
dy 2x 2
3. x + 2 y + y ln x = 0
dx
The differential equation is in the form of Final answer:
Bernoulli equation. 1
1 C
y =−
2
( ln x − 1) +
2 x
Rearrange to standard form:
dy
+ P ( x ) y = y nQ ( x ) dy
dx 4. ( cos x ) + ( sin x ) y = sin x , y ( 0 ) = 
dx
1 dy 2 − ln x
+ y= This is a linear differential equation.
y dx x x
Rearrange to standard form:
1 1 1
1− 1 − dy
Let z = y1− n = y 2
= y , dz =
2 2
y dy + P ( x) y = Q ( x)
2 dx
 cos x  dy  sin x   sin x 
  + y = 
Substitute and simplify:  cos x  dx  cos x   cos x 
2dz 2 − ln x
+ z= dy
+ ( tan x ) y = tan x
dx x x dx
dz z − ln x
+ =
dx x 2x Integrating factor:
 = e = e
P ( x ) dx ( tan x ) dx
= eln (sec x ) = sec x
Since the equation is now in the linear
differential equation form, solution for this  y =  Q ( x )  dx + C
linear differential equation applies:

## For tutorials, text:

4
<name>, <subject>, <preferred date and time>, <no. of tutees> www.wix.com/syntaxdlsu/syntax
and send to 0917 736 1385.

## Apply the solution  z =  Q ( x )  dx + C : Let v = tan  ; dv = sec2  d

dx sec2  d
( sec x ) y =  ( tan x )( sec x ) dx + C  x +  (1 + tan 2  ) = 0
( sec x ) y = ( sec x ) + C
dx sec2  d
y=
( sec x ) + C = 1 + C cos x
( )  x  sec = 0
+
( sec x ) ( sec x ) dx
 x +  sec d = 0
When y ( 0 ) =  ln x + ln ( sec  + tan  ) = c
 = 1 + ( cos 0 ) C ln  x ( sec  + tan  )  = c
  −1 
C =  =  −1 x ( sec  + tan  ) = ec = C
 cos 0 
x ( sec  + tan  ) = C
Final answer: v v2 + 1
since tan  = v = ; sec  =
y = 1 + ( − 1)( cos x ) 1 1
Substitute original variables:

5. (y− )
x 2 + y 2 dx − xdy = 0 x( )
v2 + 1 + v = C

2

## Let y = vx ; dy = vdx + xdv

  y 2 y
x    +1 +  = C
Substitute and simplify:  x x
 
( vx − )
x 2 + v 2 x 2 dx − x(vdx + xdv) = 0
 y
2

x   +1 + y = C
vxdx − x 2 (1 + v 2 )dx − vxdx − x 2 dv = 0 x
y 2 + x2
x + y =C
The equation becomes a variable separable x2
differential equation:
(1 + v 2 )dx + xdv = 0 Final answer:
y 2 + x2 + y = C
Integrate:
dx dv
 x +  (1 + v 2 ) = 0